Strategic Management Modeling for Offshore Tugboat and Support Vessel Operations: A Hybrid SWOT-TOWS Fuzzy DEMATEL-TOPSIS Framework - Ali Burçin Eke; Ozan Batmaz; Muhammed Fatih Gülen; Esma Uflaz; Özcan Arslan (Journal of Eta Maritime Science)
The maritime sector, particularly in offshore tugboat and support vessel operations, faces multifaceted strategic management challenges due to rapid technological advancements, environmental regulations, and market conditions. This paper introduces an innovative strategic decision-making framework for this industry, integrating Strengths, Weaknesses, Opportunities, and Threats (SWOT) analysis with Fuzzy Decision Making Trial and Evaluation Laboratory-DEMATEL and Order of Preference by Similarity to Ideal Solution-TOPSIS methodologies. A thorough extensive literature review and expert contributions identified 20 key factors impacting the sector across 4 SWOT categories, with balanced weights of 25.14% (strengths), 25.32% (weaknesses), 24.68% (opportunities), and 24.86% (threats). The hybrid approach uniquely highlights the interdependencies among these factors, offering a prioritized list of 8 strategic options. The analysis revealed that the WO1 strategy (focusing on cost reduction through technological innovation) emerged as the most effective strategy with a closeness coefficient of 0.798, followed by SO2 (operational efficiency enhancement) at 0.642, and ST1 (leveraging experienced crew and advanced technology) at 0.550. These results show that operational cost reduction through technological innovation and emerging market entry is a strategic priority. This study contributes significantly to the existing literature by providing a robust strategic management model tailored to address the unique challenges of offshore maritime operations. These insights are useful for improving operational efficiency for industrialists with sustainability-related concerns and for furthering their competitive advantage in an increasingly dynamic global environment. Moreover, the study also provides a replicable model that can be applied to other industries where similarly complex decisions can be made.